PERUBAHAN PARADIGMA PENGATALOGAN: PENERAPAN KONSEP FUNCTIONAL REQUIREMENTS FOR BIBLIOGRAPHIC RECORDS PADA MESIN PENCARI GOOGLE - Usman Noor, Muhammad (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2018)
Information retrieval requires an finding aid called catalog. Over time the catalog as a surrogate of documents increasingly to experience changes and paradigms. Starting from a concept that further exploit carrier cataloging to evolve in to a content cataloging, introduced as Functional Requirements for Bibliographic Records (FRBR). Without much realization it turns out Google search engine indirectly apply the concept of FRBR in the search results. The purpose of this paper is to show that the concept of cataloging that supports content management needs to be known. The method used in this paper is the literature review. The results of the study show that Google search engine shows the concept of FRBR in its search results.